Evaluation on accessibility of homestay website in Malaysia using WCAG 2.0 / Nadhirah Ariffin - Ariffin, Nadhirah (2014)
Advancement in technology has become world's largest integrity and competitiveness that rapidly grow in the intelligent technology in order to provide rich information that's available to all people all around the world. It is also known as the world of global knowledge. Nowadays, as the website becoming increasingly important to be accessible by people, many Homestay website in Malaysia is still low in term of availability and accessibility aspects to the people with disabilities. The website allows people to search all kind information and help people to find the most optimal ways in searching for a better place to stay for their vacation. All kind facilities would be given to people to make the best decision at any time. Homestay website that designed without considering the accessibility are not available and accessible to the disabled people which is important to heighten and enhance the quality of peoples knowledge via online. Furthermore, the accessibility of the website is essentials as Homestay website receives a high weight of users' activities and various kinds of users, including disabled people consistently give experience learning more about Malaysian culture and religion. This paper investigates the accessibility issues of Malaysia Homestay websites by using WCAG 2.0 guidelines.